Forced labour and economic development : an enquiry into the experience of Soviet industrialization / S. Swianiewicz - Swianiewicz, Stanisaw
En la portada: "Issued under the auspices of the Royal Institute of International Affairs" | Bibliografía: p. 304-310. Índice.